INFRASTRUCTURE RECONSTRUCTION AND ECONOMIC REVITALIZATION IN THE LIBERATED TERRITORIES: STRATEGIC APPROACHES AND PROSPECTS (Collection of research papers «ECONOMIC STRATEGY AND PROSPECTS OF TRADE AND SERVICES SECTOR DEVELOPMENT», 2026)
This article analyzes infrastructure reconstruction and economic revitalization in Azerbaijan’s liberated territories, with a focus on transport, energy, agriculture, investment, and ecological restoration. The study highlights green energy and smart city initiatives as key drivers of sustainable post-conflict development, demonstrating Azerbaijan’s reconstruction model as a significant example of regional recovery and long-term economic sustainability.
Keywords: Karabakh; infrastructure; economic development; green energy; investment; regional integration